ANALISIS TENTANG KETERAMPILAN BERFIKIR SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 1 SUNGAI AMBAWANG - Natalia, Fily Fioleta; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThinking skills or thinking skills are not only important in the world of work, education and training or research. Everyone works in the world of work both in everyday life. In the community or playground, thinking skills are very important to have. Therefore, researchers want to know more about Analysis of the thinking skills of Class VIII Students of the State High School 1 of Sungai Ambawang, Kubu Raya District.The general problem in this study was